Navigator cane / Nur Aisyah Yusof … [et al.] - Yusof, Nur Aisyah; Alias, Nur Aliya Farhani; A Halim, Athirah Fatini; Suhaimi, Nur Aleeya Syazwin; Salim, Miza Karmila; Yusof, Nur Aisyah; Aizam, Nur Farizah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Introducing the Navigator Cane, a revolutionary mobility aid designed to empower the visually impaired by addressing the challenge of safe and independent mobility. Equipped with advanced sensors, a high-resolution camera, and a dynamic screen, the Navigator Cane detects obstacles, provides real-time environmental feedback, and enhances spatial awareness. Its ergonomic rubber grip ensures comfort and stability, while the integrated speakers deliver audio cues for seamless navigation. The Navigator Cane features a dedicated button to start recording video, providing valuable evidence in case of accidents or incidents, thus increasing the user's safety and security during travel. With a rechargeable battery, charger socket, and SD card slot for extended use and data storage, the Navigator Cane offers unparalleled support and security for independent travel. This innovative mobility aid not only enhances the quality of life for visually impaired individuals but also has strong potential for commercialization, meeting a critical need in the market for innovative mobility aids.